Respuesta :

Answer:

6[tex]\sqrt{3}[/tex]

Step-by-step explanation:

We have to use Pythagoras' identity twice to find y

The square on the hypotenuse is equal to the sum of the squares on the other two sides.

In right triangle MUT to find TU

TU² + 3² = 6², that is

TU² + 9 = 36 ( subtract 9 from both sides )

TU = 27 ( take the square root of both sides )

TU = [tex]\sqrt{27}[/tex] = [tex]\sqrt{9(3)}[/tex] = 3[tex]\sqrt{3}[/tex]

In right triangle NUT to find y

y² = 9² + (3[tex]\sqrt{3}[/tex] )² = 81 + 27 = 108 ( take the square root of both sides )

y = [tex]\sqrt{108}[/tex] = [tex]\sqrt{36(3)}[/tex] = 6[tex]\sqrt{3}[/tex]